(Keynote) Pyrochemical Process in Molten Salts for Spent Nuclear Fuel Reprocessing and Radioactive Waste Treatments. (23rd July 2018) - Fujita, Reiko
Abstract : The pyrochemical process in molten salts for spent fuel reprocessing and radioactive waste treatment has been developed since 1988. The pyrochemical process for metallic fuel reprocessing has been started using electrorefining. The electrowinning for spent oxide fuel in molten salts has been developed since 1994. The radioactive waste treatment such as treatment process of metallic waste contaminated by uranium and chemical trap materials in uranium enrich plant. Zirconium recycle for zircaloy waste from LWR was based on the spent fuel reprocessing. A treatment process for debris in Fukushima Daiichi Nuclear Power Plant recently has been just started. This paper reviews pyrochemical process for spent fuel reprocessing and radioactive waste treatment.